Enhanced UV-C resistance through light-activated zinc-cysteine complex formation - Füleky, Martin; Molnárová, Katarína; Novák, Jan; Vodová, Milada; Lenža, Libor; Nejdl, Lukáš (Springer London, 2025)
Ultraviolet (UV) radiation is a significant environmental stressor that affects the growth, physiology, and biochemical integrity of various organisms. This study investigates the potential protective effects of a zinc-cysteine (Zn-Cys) complex against UV-C radiation, with a focus on its impact on selected microalgae (Coccomyxa peltigerae and Parachlorella kessleri) and maize (Zea mays L.). We demonstrate that exposure of the Zn-Cys complex to UV-C (254 nm) results in the formation of fluorescent photoproducts, which exhibit UV-protective properties. The study reveals that Zn-Cys significantly mitigates UV-induced stress. In both microalgae species, the Zn-Cys complex enhanced growth even under UV exposure, with the 20% concentration showing the most robust protective effects. Further hyperspectral imaging confirmed the protective mechanism of Zn-Cys by monitoring changes in light reflectance in Parachlorella kessleri, indicating reduced photosynthetic efficiency and structural alterations induced by UV exposure, while Zn-Cys significantly mitigated these effects. In addition, in maize plants (Zea mays L.), Zn-Cys treatment preserved chlorophyll content and reduced polyphenol accumulation, indicating reduced oxidative stress. These findings highlight the potential of the Zn-Cys complex as a sustainable and cost-effective strategy for UV protection in both terrestrial and extraterrestrial agriculture, advancing our understanding of plant adaptation to extreme environments.
Keywords: Hyperspectral imaging; Microalgae; Plants; Spectrophotometry; UV protection